Managerial Ownership Moderates The Relationship Between Ios And Stock Price - Yuliza, Arma (Accounting and Business Journal, 2022)
This study was conducted at the Indonesian Stock Exchange with the aim of determining the ability of managerial ownership to moderate the relationship between investment opportunity sets and stock prices. Investment opportunity sets were assessed using three Market to book value of equity (MVE) ,Book to market value of assets (MVA), Earnings to price ratios (EP) and Managerial Ownership (MO). This research is descriptive quantitative conducted using secondary data obtained from the official website of the Indonesian capital market and the official website of the sample companies. Data analysis was conducted using multiple linear regression analysis with the value of the moderation variable using the interaction between the independent variable and the moderation variable. From the results of the data analysis that has been carried out, it was obtained that managerial ownership was not able to moderate the relationship between the investment opportunity set and stock prices.